Role of the Immune Microenvironment in SARS-CoV-2 Infection. (3rd May 2021) - Ye, Chih-Hung; Hsu, Wen-Lin; Peng, Guan-Ru; Yu, Wei-Chieh; Lin, Wei-Chen; Hu, SuiYun; Yu, Shu-Han
Severe acute respiratory syndrome coronavirus (SARS-CoV-2) first emerged in December 2019 in Wuhan, China, and has since spread rapidly worldwide. As researchers seek to learn more about COVID-19, the disease it causes, this novel virus continues to infect and kill. Despite the socioeconomic impacts of SARS-CoV-2 infections and likelihood of future outbreaks of other pathogenic coronaviruses, options to prevent or treat coronavirus infections remain limited. In current clinical trials, potential coronavirus treatments focusing on killing the virus or on preventing infection using vaccines largely ignore the host immune response. The relatively small body of current research on the virus indicates pathological responses by the immune system as the leading cause for much of the morbidity and mortality caused by COVID-19. In this review, we investigated the host innate and adaptive immune responses against COVID-19, collated information on recent COVID-19 experimental data, and summarized the systemic immune responses to and histopathology of SARS-CoV-2 infection. Finally, we summarized the immune-related biomarkers to define patients with high-risk and worst-case outcomes, and identified the possible usefulness of inflammatory markers as potential immunotherapeutic targets. This review provides an overview of current knowledge on COVID-19 and the symptomatological differences between healthy, convalescent, and severe cohorts, while offering research directions for alternative immunoregulation therapeutic targets.